Enhancing user experience in interactive directory kiosk with virtual walkthrough - Senan, Norhalina; Lim, Sie Hui; Suparjoh, Suriawati; Othman, Muhammad Fakri (Penerbit UTHM, 2017)
Interactive kiosk is an information platform featuring specialized hardware and software which can be found almost in public exhibition. It serves the purpose of providing information to users for communication, health, commerce, entertainment, and education. Directory kiosk is other types of information kiosk that allows the user to find certain location or rooms within the building. This kiosk becomes a centre of attraction and it is located at the main entrance of the building and publicly accessible by the user to find information. The users are also diverse in terms of their skills, experience and expectation in using the kiosk (Maguire, 1999). For that, instead of achieving the usability goals, providing a quality of experience in kiosk development process is very crucial and become a challenge to the user experience (UX) and user interface (UI) designers.